An energy-dispersive X-ray fluorescence method for analysing Fe and Zn in common bean, maize and cowpea biofortification programs - Guild, Georgia E.; Paltridge, Nicholas G.; Andersson, Meike S.; Stangoulis, James C.R. (Springer, 2017)
Background and aims